Source identification and ecological risk assessment of heavy metal pollution in sediments of Setiu wetland, Malaysia. Issue 1 (4th March 2022) - Talukder, Rasendra; Rabbi, Md Hasim; Baharim, Nor Bakhiah; Carnicelli, Stefano
Abstract: We investigated the source, contamination level and the potential ecological risk of heavy metals (Al, Cr, Fe, Ni, Cu, Zn, As, Cd and Pb) in the Setiu wetland area, one of the largest natural wetlands on the East Coast of peninsula Malaysia. To do this, we collected surface sediments between 0 and 10  cm depth from 27 locations. These locations covered the major habitat types in the wetland, specifically: Setiu lake, Setiu lagoon, Setiu estuary and Setiu river. Heavy metals were then measured using a closed digestion method which employs high temperatures and strong acids. Analysis of the enrichment factor (EF), Geo-accumulation Index (Igeo ) and Contamination Factor (CF) showed a low contamination level of all heavy metals in Setiu wetland besides Cr. In the Setiu lagoon and Setiu river habitats, similar analyses categorised the contamination level of Cr as moderately enriched. Overall, the Pollution Load Index (PLI) classified the Setiu river as un- or moderately polluted. All other habitats were unpolluted by heavy metals. Multivariate analyses suggest that the metals: Al, Mn, Fe, Cu, Zn and Pb originated from the lithogenic process. In contrast, Cr was derived from both lithogenic processes and anthropogenic activities whilst Cd and Ni came from anthropogenic activities into the Setiu wetland ecosystems. Additionally, finer grain size (MS) and higher TOC in the sediments of Setiu lake & Setiu river also facilitated the accumulation of the metal in sediments.